2013
DOI: 10.3141/2385-08
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to Modeling Large-Scale Transitions to Alternative Fuels and Vehicles

Abstract: A large-scale transition to alternative fuels and vehicles is challenging. New modeling approaches are necessary to supplement existing models, such as MARKAL. One promising approach is simulation gaming. Simulation gaming has been used extensively in many fields, most conspicuously in military applications, to provide insights into the dynamics of uncertain processes. A large-scale game to simulate transitions to alternative fuels and vehicles was developed to explore the potential of this approach. Prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…There is a drastic increase of 2.3 times from the original weight of Emotion. This is in line with previous works that showed that vehicles become a tool that can bring emotional benefits to users [5][6][7][8]. The emotional benefit can be something personal to the drivers such as pleasure, pride and negative embarrassment [45].…”
Section: Discussion and Practical Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…There is a drastic increase of 2.3 times from the original weight of Emotion. This is in line with previous works that showed that vehicles become a tool that can bring emotional benefits to users [5][6][7][8]. The emotional benefit can be something personal to the drivers such as pleasure, pride and negative embarrassment [45].…”
Section: Discussion and Practical Implicationssupporting
confidence: 90%
“…In Indonesia, four-wheeled vehicles are still a product of people's dreams. Previous studies show that cars not only function as a means of transportation to facilitate one's mobility, but have become a tool to fulfill emotional needs such as self-expression [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%